An instrumental analysis of /e/, /ɛ/, /o/ and /ɔ/ in Malacca Portuguese Creole / Siti Raihan Rosli - Siti Raihan , Rosli (2018)
Previous work on the vowel system of Malacca Portuguese Creole (MPC) has highlighted that there are overlaps between particular vowels (Pillai, Chan & Baxter, 2015), therefore suggesting the possibility of phonological instability. However, these studies have been inconclusive about the status of /e/, /ɛ/, /o/ and /ɔ/. Hancock (2009), for example, suggests that /e/ and /ɛ/ contrast only in two words while Baxter (1988) suggests that the use of these vowels are not systematic, contrasting only before /t/, /s/ and /z/. Similarly, Baxter (1988) also posits that /o/ and /ɔ/ contrast before /t/, /d/ and /l/. However, there has thus far not been any empirical evidence to show the extent and status of the contrast between these vowels. This study therefore, instrumentally examines the vowels /e/, /ɛ/, /o/ and /ɔ/ to investigate if there is a difference in vowel quality between the vowels and to also determine their phonological status in MPC. Recordings of 1,141 words containing /e/, /ɛ/, /o/ and /ɔ/ from two MPC dictionaries (Baxter & de Silva, 2004; Scully & Zuzarte, 2004) and the glossary in Singho et al (2016) by five native speakers of MPC, were orthographically transcribed and annotated using Praat, version 5.4.18 (Boersma & Weenik, 2015), a speech synthesis and analysis programme. The vowels were then analysed using the Formant Frequency Model, which posits that the lower the F1, the higher the vowel and the higher the F2, the more front the vowel is. Besides that, a two-tailed independent sample t-test and ANOVA were conducted to the overall and individual measurements of F1 and F2 between /e/ and /ɛ/, and /o/ and /ɔ/. Based on the findings, the overall placement of /e/, /ɛ/ and /o/ are in accordance to Klein (2006) but /ɔ/ appears to be more fronted. Although findings indicate a significant difference, F1 reported a high practical significance while F2 reported a low practical significance. This means that the key difference between the vowels lies in height rather than fronting. Nevertheless, overlaps are apparent between the five native speakers, which suggest the possibility of speaker variance and the interchangeable use of /e/ and /ɛ/ as well as /o/ and /ɔ/. There was also evidence of individual variance where speakers have a tendency of pronouncing the /ɔ/ sound differently from one word to another word. Besides that, Baxter’s (1988) claim of vowel harmony is supported by findings of the present study since /e/ and /o/ did precede high vowels. However, this was not the case for /ɛ/ and /ɔ/ since a schwa is more likely to follow compared to low vowels. Additionally, 30 out of 37 borrowed words originated from Malay. Despite having English borrowings in MPC, there is a notable difference in pronunciation. From the findings, it appears that the vowels /e/, /ɛ/, /o/ and /ɔ/ are distinct phonemes in Malacca Portuguese Creole.